Perilaku ibu dalam pemanfaatan persalinan penundaan pemotongan tali pusat sampai 24 jam - Desi Nurlaela Mulyana; Umi Salamah; Djati Wulan Kusumo (Universitas Muhammadiyah Semarang, 2020)
The method of delaying cutting the umbilical cord after the baby is born and letting the cord out completely and then cut after 24 hours has not been implemented in all health facilities. Klinik Utama Anny Rahardjo has been implementing since 2012. The purpose of this research is to know the mother's behavior in the utilization of delivery delay cutting of the umbilical cord up to 24 hours at Klinik Utama Anny Rahardjo East Jakarta in 2017. The method used in this research is a descriptive qualitative method of describing mothers who have utilized this delivery at Klinik Utama Anny Rahardjo. This study amounted to 13 people consisting of 7 informants and 6 key informants. The result of research that mother's behavior is good enough, age, job, distance, and cost don't influence mother's behavior, while education, knowledge, attitude, family support, and health worker influence mother's behavior, in the utilization of delivery delay cord cutting up to 24 hours. It is suggested for Klinik Utama Anny Rahardjo to provide more information so that the mother's knowledge is better, for other researchers it is suggested that the research method use quantitative to get more samples, and for health service to follow up the development of science in the field of this method of delivery.